White Paper of the Society of Computed Body Tomography and Magnetic Resonance on Dual-Energy CT, Part 3: Vascular, Cardiac, Pulmonary, and Musculoskeletal Applications. Issue 1 (January 2017) - De Cecco, Carlo N.; Schoepf, U. Joseph; Steinbach, Lynne; Boll, Daniel T.; Foley, W. Dennis; Kaza, Ravi K.; Bolus, David N.; Morgan, Desiree E.; Sahani, Dushyant V.; Shuman, William P.; Siegel, Marilyn J.; Vrtiska, Terri J.; et al.
Abstract : Abstract: This is the third of a series of 4 white papers that represent Expert Consensus Documents developed by the Society of Computed Body Tomography and Magnetic Resonance through its Task Force on dual-energy computed tomography. This paper, part 3, describes computed tomography angiography and thoracic, cardiac, vascular, and musculoskeletal clinical applications. At the end of the discussion of each application category (vascular, cardiac, pulmonary, and musculoskeletal), we present our consensus opinions on the current clinical utility of the application and opportunities for further research.